Futures Markets and Macroeconomics: Empirical Evidence from China - Gao, Tian Chen; Gao, Hui (Archives of Business Research, 2023)
This paper uses the methods of Granger causality test, cointegration relationship test, error correction model and shock response function in cointegration correlation theory, and uses the monthly data from 2003.1 to 2023.5 to study the role and influence of futures market variables (price index, total turnover, total open interest) on sixteen macroeconomic variables. The results show that the three indicators of the futures market have a guiding effect on industrial added value, net export, fiscal revenue and fiscal expenditure at the same time. The price index and total turnover also have a guiding effect on the interbank 7-day interest rate and the RMB real effective exchange rate index. The total turnover and total open interest also have a strong guiding effect on the total import and export volume, the investment amount of fixed assets, and the total retail sales of social consumer goods. The price index also has a strong guiding effect on the producer price index, total loans, and the exchange rate of the US dollar against the RMB. The total open interest also has a strong guiding effect on the total loan. The cointegration test and error correction model show that in the short and long term, the futures market variables have a strong or weak quantitative impact on twelve macro variables, and the shock response function curve shows that the futures market variables have different impact effects on twelve macro variables. It shows that the futures market has a relatively strong impact on the macroeconomy, but there is still much room for improvement in the scope and depth of influence. It is suggested that the futures market should make efforts in terms of variety expansion, internationalization and supervision to further promote the comprehensive development of the domestic macroeconomy.